The use of over-the-counter medication by elderly medical in-patients. Issue 865 (November 1997) - Batty, G. M.; Oborne, C. A.; Swift, C. G.; Jackson, S. H.
Abstract : Use of over-the-counter (OTC) medications by elderly patients is often not identified. This survey was performed to study the use of OTCs by medical in-patients aged 65 and over. Data on the use of OTC medications before and during hospital admission were collected by questioning patients and case notes were examined for documentation of their use of OTC medications. OTC medications were used by 44 of 138 (32%) patients interviewed. Patients used a total of 70 OTC medications before admission and six OTC medications were being used during hospital admission. There was no documentation of pre-admission and in-hospital OTC medicine use in the clinical notes and patients had little knowledge of the potential harm some products can cause. As more products become available over the counter, doctors should record their use in patients' notes and patients should be encouraged to seek professional advice before purchasing OTC medicines and to read the product information leaflets.